Using pyroelectric sensors to detect continuous infrared radiation - Heydarianasl, Mozhde (Penerbit UTM Press, 2014)
This paper focuses on an optimized method for detecting continuous infrared rays make use of Pyroelectric devices. Now, Pyroelectric devices are usually very sensitive to changes in infrared radiation in the presence of an object when transfers or radiation is connected or disconnected. In this new approach, the thermo-electric cooler is employed to active temperature sensors instead of conventional modulation. They use mechanical parts, which are complex and un-reliable. The most of the sensor consists of a number of important restrictions, which are expected to be eliminated by a new method in this study. To simulate the thermal and electrical behavior of the detector, the equivalent electrical circuit is needed that will be proposed.The practical results of Pyroelectric sensor are sent to a computer by a digital oscilloscope, and then they are monitored and analyzed. After that, the model is simulated with MATLAB software. Finally, practical and theoretical results compared with each other and a good agreement of them is shown and confirms the validity of the model.